Filmmaking for teens : pulling off your shorts - Lanier, Troy, 1967-; Nichols, Clay, 1967- (Studio City, CA : Michael Wiese Productions, 2010)
A guide to filmmaking for teens that covers picking a subject, writing a script, production, schedules, expenses, directing, equipment, lighting, sound, editing, and distribution, and provides tips on techniques.
Includes index.
Keywords: Short films -- Production and direction